Relation Between Hepatitis C Virus Exposure and Risk of Osteoporosis: A Nationwide Population-Based Study. Issue 47 (November 2015) - Chen, Chien-Hua; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Abstract: The effect of hepatitis C virus (HCV) exposure on bone mineral density without advanced liver disease remains debated. Thus, we assessed the relation between HCV exposure and the risk of osteoporosis. From 2000 to 2011, patients aged >20 years with HCV exposure were identified from the Longitudinal Health Insurance Database 2000. Of the 51, 535 sampled patients, 41, 228 and 10, 307 patients were categorized as the comparison and the HCV exposure cohorts, respectively. The overall incidence of osteoporosis in the HCV exposure cohort was higher than in the comparison cohort (8.27 vs 6.19 per 1000 person-years; crude hazard ratio = 1.33, 95% confidence interval = 1.20–1.47). The incidence of osteoporosis, higher in women than in men, increased with age and comorbidity of hypertension, hyperlipidemia, and heart failure. The risk of developing osteoporosis was significantly higher in the HCV exposure cohort than in the comparison cohort after adjusting for age, sex, diabetes, hypertension, hyperlipidemia, heart failure, stroke, and cirrhosis. However, the risk of osteoporosis contributed by HCV decreased with age and the presence of comorbidity. Furthermore, the risk of osteoporotic fracture did not differ significantly between patients exposed to HCV and the comparison cohorts. HCV increases the risk of osteoporosis, but no detrimental effect on osteoporotic fracture was observed in this study. Furthermore, HCV may be less influential than other risk factors, such as hypertension, hyperlipidemia, and heart failure, in contributing to the development of osteoporosis.